A contribution for the limnological knowledge of basaltic knickzones - E. M. Brambilla; A. M. C. Ruocco; M. G. Nogueira (Brazilian Journal of Biology, 2017)
Abstract The knickzones are defined as locally steep riverbed segments, such as a convex reach in a concave-up longitudinal profile. They are worldwide distributed and geologically well studied, but despite their distinctiveness as a particular kind of macrohabitat there is a notorious lack of ecological knowledge. In this context, this research proposal aims to provide a physical description, in terms of kind of habitats, and a limnological characterization of a basaltic knickzone. Information is based on a case study carried out in the Sapucaí-Mirim River, Southeast Brazil. Samplings were performed in three different habitats well represented in the knickzone (runs, riffles and pools) during rainy and dry conditions. A clear discrimination in terms of habitat type and seasonality was demonstrated through a principal component analysis. Pools exhibited higher amplitude of variation for most limnological parameters when compared to runs and riffles, probably due to a great influence of the internal metabolism (photosynthetic production and community respiration). Despite of their geological ancient formation and the little understanding of their ecological role, the knickzones are in imminent threat in several regions of the world by hydropower dams implementation. The lack of ecological information on knickzones is probably due to inherent access difficulties and how to compare the distinct kinds of habitats. Thereby, further studies should be encouraged.